2008
DOI: 10.2174/1874315300801010068
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Smear Negative And Culture Positive Results Among Pulmonary Tuberculosis Patients in Mwanza, Tanzania

Abstract: Background: Smear negative and culture positive results in pulmonary tuberculosis are not uncommon yet the underlying factors are not well established. Objective: To determine factors associated with smear negative and culture positive results. Methods: Pulmonary tuberculosis patients were consecutively recruited for 12 months from five health facilities in Mwanza region, Tanzania. Sputum examinations were done at the recruitment centre and at the TB reference laboratory using Auramine O technique. Culture was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Different risk factors have different impacts on the occurrence and diagnosis of SNPT. Studies have shown different risk factors for the occurrence of SNPT [9, 24, 25]. But, there is limited information about factors associated with SNPT in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Different risk factors have different impacts on the occurrence and diagnosis of SNPT. Studies have shown different risk factors for the occurrence of SNPT [9, 24, 25]. But, there is limited information about factors associated with SNPT in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence of smear negative culture positive PTB saw in a study conducted in Ethiopia at St. Peter TB specialized Hospital, 43/247 (17.4%) patients whose smears negative for acid-fast bacilli found to be positive for mycobacterial culture [9]. Similarly, higher prevalence of (17.5%), (26.8% ) and (27.8%) smear negative culture positive results seen in Kenya, Tanzania and Peru respectively [10][11][12]. The variation of prevalence of SNPT may be a due difference of study population, the status of the patient and method of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A presumptive diagnosis of AFB sputum smear-negative PTB was made in 41.8% (173) of all study subjects, and patients started on anti-TB treatment as recommended by the Tanzania NTLP. The remaining 58.2% (240) patients were assumed to have other forms of respiratory diseases and were treated accordingly [11].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of this method varies and depends upon the collection of sufficient sputum, proper preparation of smears, good staining technique, careful examination of smears, and availability of a good microscope. Several methods have been tried to improve smear microscopy for AFB [3]. On the other hand, Light Emitting Diode (LED) microscopes are less expensive, require less power and are able to run on batteries, the bulbs have a very long halflife.…”
Section: Introductionmentioning
confidence: 99%